Periodic blinking manipulation of magnetic Janus particles with a tunable electromagnetic field for rapid sensing of extracellular vesicles - Chuang, Han-Sheng; Pham, Thi Thanh Huong; Chou, Yu-Hsuan; Huang, Chi-Ying F.; Tu, Ting-Yuan; Yang, Tai-Hua; Wang, Jhih-Cheng (Frontiers in Bioengineering and Biotechnology, 2025)
Detecting small biological molecules is challenging due to their tiny size, vulnerability, and low concentrations in samples. Bead-based biosensors are frequently used as probes but require tedious processing or expensive instruments. By combining magnetic Janus particles (MJPs) and an electromagnetic device, we successfully built an active diagnostic tool for the rapid sensing of small extracellular vesicles (sEVs). We observed that the system can be altered according to particle size, distance between MJPs and the electromagnet, fluid viscosity, and magnetic field strength. By modulating the driving frequency from low (3 Hz) to high (22 Hz), the MJPs gradually lose their synchrony with the external magnetic field after exceeding a certain threshold termed cutoff frequency. The novel sEVs sensing MJP system was characterized through both theoretical and experimental methods, showing reliable performance in identifying the cancer cell OECM-1-derived sEVs using the CD63 surface marker. A decent sEV concentration of 2.9 × 109 particles mL−1 was reached and a high specificity was also observed. This approach opens a door for the realization of disease screening, such as cancer, using intact exosomes from body fluids without sophisticated processing. These findings provide insight into the future use of MJPs as point-of-care testing tools for liquid biopsy.